Metode Qur’ani Dalam Mengatasi Sikap Fanati - Aminullah Cik Sohar; M Randicha Hamandia (Wardah, 2019)
Abstract : Fanatic is a view that does not have a theoretical backing or a foundation of reality, but is deeply embraced so that it is difficult to straighten or change. Fanatic attitudes arise in the form of excessive trust in the teachings adopted. A fanatic person in the teachings that he professes rejects all the different forms of teaching from his beliefs. The problem is how is the method of guidance and counseling qurani in overcoming fanatical attitudes. Fanatic causative factors according to the Koran are internal factors and external factors. While the Quranic method in overcoming fanatic attitudes is good teaching methods and dialogue methods. Keywords: Qur’ani method, fanatic